Speed-sintering and the mechanical properties of 3–5 mol% Y2O3-stabilized zirconias - Lubauer, Julia; Schuenemann, Fernanda Haverroth; Belli, Renan; Lohbauer, Ulrich (Odontology, 2023)
Ever faster workflows for the fabrication of all-ceramic restorations are of high economic interest. For that purpose, sintering protocols have been optimized for use in modern sintering furnaces, the so-called speed-sintering. However, conventional furnaces are still the most widely used equipment to sinter zirconia restorations. In this in-vitro study, we evaluated the feasibility of a speed-sintering protocol using a conventional sintering furnace to sinter different dental zirconias (stabilized with 3 mol% up to 5.4 mol% Y2O3) in comparison to a conventional sintering program. The properties evaluated were Young’s modulus, Poisson’s ratio, density, biaxial flexural strength, and fracture toughness. We show here that despite differences being dependent on material, the physical and mechanical properties of speed-sintered zirconia are comparable to those obtained by the conventional sintering.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Flexural strength; Mechanical tests; Yttria-stabilized tetragonal zirconia